Equilibrio contractual y trasparencia en la era digital: análisis de las cláusulas leoninas en los contratos de adhesión - Mera Canché, Johan Ariel (2025)
This research addresses the challenges faced by consumers in the Ecuadorian digital environment due to adhesion contracts, which are characterized by being pre-established and non negotiable. In the digital age, these contracts are essential for commercial transactions but often include abusive or 'leonine' clauses that limit users' rights, disproportionately favoring companies and creating contractual imbalances. The objective of the research was to analyze the prevalence and impact of leonine clauses in digital adhesion contracts in Ecuador, with the aim of proposing measures to promote transparency and contractual balance. The study used a qualitative approach, analyzing adhesion contracts in key sectors such as telecommunications, banking, and entertainment platforms. The documentary review was complemented with interviews of experts in digital law and consumer protection, allowing for an assessment of contractual practices and their impact on users. The results revealed that abusive clauses are common in digital contracts, highlighting practices such as unilateral modification of terms, lack of refunds for unused services, imposition of hidden penalties, and ambiguous treatment of personal data. These clauses affect consumers' ability to make informed decisions, compromise their financial autonomy, and violate their privacy. Additionally, the complexity and technical language of the contracts hinder comprehension, increasing user vulnerability. The study concluded that adhesion contracts used by digital service providers in Ecuador contain leonine clauses that create a contractual imbalance by disproportionately favoring companies, thus affecting consumers' rights.